(untitled) (Khairulummah, 2024)
Abdel Rahman Al-Sharqawi presented moral values ​​and the importance of humanity in his novels, reflecting the circumstances of his time. In his novel, "The Land and the Peasant," he raised his voice against the work of the peasant class and their right to their wages. He also raised his voice against the authorities for not granting them their rights. The most important influential factor presented by Abdel Rahman Al-Sharqawi in his novels is his humanism. He presents moral values ​​regarding the importance and value of humanity in life throughout his novels, defending rights and truth, humanity, and the Egyptian character. Abdel Rahman Al-Sharqawi addressed most social topics and addressed people’s concerns and problems. The importance of this topic, I have chosen topic about: "Humanism in the novels of the great writer Abdel Rahman Al-Sharqawi"